Coherence in EU competition law - Sauter, Wolf (Oxford : Oxford University Press, 2016)
Sauter examines how competition law maintains its coherence. He charts the historical development of the EU competition regime and its path to decentralised enforcement, as well as studying the coherence of the regime's goals, boundaries, rules, and exceptions.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 10, 2016).
Keywords: Antitrust law -- European Union countries; Law; Laws of specific jurisdictions & specific areas of law